Mixed Convection in a Lid-Driven Cavity with Triangular Corrugations and Built-in Triangular Block - Kumar, Sudhanshu; Panda, Sibasish; Gangawane, Krunal M.; Vijayan, Aparna; Öztop, Hakan Fehmi; Nidal-Abu Hamdeh (Wiley-V C H Verlag Gmbh, 2022)
The influence of triangular surface corrugations on the mixed convection characteristics in a tall lid-driven cavity for non-Newtonian power-law fluids is reported. In particular, numerical experimentations are executed for a range of parameters, such as aspect ratio of cavity, number of triangular corrugations, Richardson numbers, Prandtl numbers (Pr), power-law indexes, and at a constant Grashof number. The corrugation number seems to be the maximum impact for higher Prandtl number fluids. For taller cavities, higher Nusselt number values were obtained for Pr = 100. Triangular corrugations showed a modest change in the heat transfer augmentation in most of the considered parameters.
Keywords: Mixed convection; Non-Newtonian power-law viscosity model; Richardson number; Triangular blocks; Triangular corrugations